"Experiences with disclosure of HIV-positive status to the infected child": Perspectives of healthcare providers in Dar es Salaam, Tanzania - Adellah Sariah; Joan Rugemalila; Magreat Somba; Anna Minja; Margareth Makuchilo; Edith Tarimo; David Urassa; Helen Siril (BMC, 2016)
Abstract Background The specific age to which an HIV infected child can be disclosed to is stipulated to begin between ages 4 and 6 years. It has also been documented that before disclosure of HIV positive status to the infected child. Health care providers should consider children's cognitive-developmental ability. However, observation and situation analysis show that, health care providers still feel uncomfortable disclosing the HIV positive status to the infected child. The aim of the study was to explore healthcare providers' experiences in disclosure of HIV-positive status to the infected child. Methods A qualitative study involving 20 health care providers who attend HIV-positive children was conducted in September, 2014 in Dar es Salaam, Tanzania. Participants were selected from ten HIV care and treatment clinics (CTC) by purposive sampling. An interview guide, translated into participants' national language (Kiswahili) was used during in-depth interviews. Sampling followed the principle of data saturation. The interviews focused on perspectives of health-care providers regarding their experience with paediatric HIV disclosure. Data from in-depth interviews were transcribed into text; data analysis followed qualitative content analysis. Results The results show how complex the process of disclosure to children living with HIV can be to healthcare providers. Confusion was noted among healthcare providers about their role and responsibility in the process of disclosing to the HIV infected child. This was reported to be largely due to unclear guidelines and lack of standardized training in paediatric HIV disclosure. Furthermore, healthcare providers were concerned about parental hesitancy to disclose early to the child due to lack of disclosure skills and fear of stigma. In order to improve the disclosure process in HIV infected children, healthcare providers recommended further standardized training on paediatric HIV disclosure with more emphasis on practical skills and inclusion of disclosure content that is age appropriate for children with HIV. Discussion The disclosure process was found to be a complex process. Perspectives regarding disclosure in children infected with HIV varied among healthcare providers in terms of their role in the process, clear national guidelines and appropriate standardized training for paediatric disclosure. Consistent with other studies, healthcare providers reported difficulties during disclosure because parents /guardians largely fear blame, social stigma, child's negative emotional reaction when disclosed to and have concerns about the child being too young and immature to understand the HIV condition. Conclusions In order to prevent inconsistencies during the disclosure process, it is important to have in place clear guidelines and standardized paediatric HIV disclosure training for healthcare providers. This would help improve their skills in paediatric disclosure, leading to positive health outcomes for children infected with HIV.